1999
DOI: 10.1002/1529-0131(199906)42:6<1232::aid-anr21>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis of the finger joints: A comprehensive approach comparing conventional radiography, scintigraphy, ultrasound, and contrast-enhanced magnetic resonance imaging

Abstract: Objective. A prospective study was performed comparing conventional radiography, 3-phase bone scintigraphy, ultrasound, and magnetic resonance imaging (MRI) with precontrast and dynamic postcon-trast examinations in 60 patients with various forms of arthritis including rheumatoid arthritis (RA), spondyl-arthropathy, and arthritis associated with connective tissue disease. Methods. A total of 840 finger joints were examined clinically and by all 4 imaging methods. Experienced investigators blinded to the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
283
1
47

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(355 citation statements)
references
References 29 publications
19
283
1
47
Order By: Relevance
“…This illustrates that the information on joint destruction provided by CR is associated with a considerable delay. In accordance with results of earlier studies (6)(7)(8)12), we observed that the sensitivity of MRI with respect to visualization of bone erosions was superior to that of CR. Furthermore, MRI detected erosive progression in more bones than did CR (i.e., MRI was more sensitive to change).…”
Section: Discussionsupporting
confidence: 92%
“…This illustrates that the information on joint destruction provided by CR is associated with a considerable delay. In accordance with results of earlier studies (6)(7)(8)12), we observed that the sensitivity of MRI with respect to visualization of bone erosions was superior to that of CR. Furthermore, MRI detected erosive progression in more bones than did CR (i.e., MRI was more sensitive to change).…”
Section: Discussionsupporting
confidence: 92%
“…It is important to emphasize that some features of these definitions, for example, the description of the secondary epiphyseal ossification center in definition 2, do apply to the immature skeleton of a growing child but will not be detectable in the fully ossified bone of an older adolescent. Upon rescoring, a Likert scale score of 4 …”
Section: Resultsmentioning
confidence: 99%
“…Imaging can add important information to the clinical examination in rheumatology, and this is no different in pediatric rheumatology (1)(2)(3)(4)(5)(6). With new treatments, the induction of sustained remission is possible for an increasing percentage of children but cannot always be reliably demonstrated on clinical examination alone (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have described improved sensitivity for detection of joint effusion, synovitis, and bone erosions in RA joints with the use of ultrasound (US) as compared with conventional clinical and radiologic methods (1)(2)(3). Because ultrasonography is a relatively easily accessible and lowcost method, the technique can be used not only by radiologists, but also by trained rheumatologists.…”
mentioning
confidence: 99%